Time to be counted: COVID-19 and intellectual and developmental disabilities-an RSC Policy Briefing - Annette Majnemer; Patrick J. McGrath; Jennifer Baumbusch; Chantal Camden; Barbara Fallon; Yona Lunsky; Steven P. Miller; Genevieve Sansone; Tim Stainton; John Sumarah; Donna Thomson; Jennifer Zwicker (Canadian Science Publishing, 2021)
The COVID-19 pandemic has impacted the lives and well-being of all people globally, with consequences being observed across all domains from physical and mental health, to education and employment outcomes, to access to community supports and services. However, the disproportionate impact of the COVID-19 pandemic and its associated public health restrictions on individuals with intellectual and developmental disabilities (IDD) has largely been overlooked. Not only do people with IDD have a greater risk of severe complications and death from the virus as shown in large-scale studies, but they also face significant short- and long-term consequences of COVID-related public health measures on their mental health and well-being. At a time when this vulnerable population is already feeling undervalued, ignored, and forgotten, it is imperative that the risks facing adults and children with IDD-as well as their families and caregivers-are recognized, valued, and addressed through a disability-inclusive approach to Canada's pandemic policy response planning. This requires both a mainstreaming of disability inclusion into all COVID-19 response and recovery policies as well as disability-specific policies to address the unique barriers and challenges encountered by people with IDD during the pandemic. The recommendations in this policy briefing aim to achieve a more inclusive, accessible, and sustainable Canada for people with IDD both during and after the pandemic-an approach that will result in benefits for all of society.